Ultra-Low Dose Computed Tomography Imaging in Quantifying Bone Trauma and Disorders: A Cross-Sectional Study - Fariba Zarei; Seyedeh Marzieh Ahmadi; Saber Dehbani-Zadeh; Anahita Jafari; Vyas Akondi; Sabyasachi Chatterjee; Seyed Alireza Mirhosseini; Rezvan Ravanfar Haghighi (Iranian Journal of Medical Sciences)
Background: X-ray computed tomography (CT) is a standard tool for diagnosing bone abnormalities. CT dose optimization is strongly recommended, due to the stochastic effects of x-ray. This study aims to assess the effectiveness of ultra-low-dose CT (ULD-CT) imaging, reconstructed using an Iterative Reconstruction (IR) algorithm, in detecting bone trauma and disorders.Methods: In the present cross-sectional study, 71 patients with CT requests for spine or extremity (limb) bone underwent scanning using standard dose (SD) and ULD-CT protocols, in Shahid Faghihi Hospital, Shiraz, Iran from June 2019 to June 2020. The SD and ULD-CT protocols used 120 kVp and 80 kVp, respectively. The CT images were reconstructed using the standard and IR algorithms. CT dose indices, including the volume CT dose index (CTDIvol), dose-length product (DLP), and effective dose (ED), were employed. To assess image quality, a five-point scoring system was used. The sensitivity and specificity of the ULD-CT images were calculated.Results: The findings indicated that ULD-CT images accurately identified 113 out of 118 bone trauma and disorders. The quality of ULD-CT images received “very good”, “good” and “acceptable” scores for both spine and extremity (limb) bones. The sensitivity and specificity of ULD-CT images for bone trauma and disorders were 67%–95% and 100%, respectively, with about a 98% dose reduction.Conclusion: The ULD-CT protocol for bone imaging achieved a remarkable dose reduction, while the image quality was reported as acceptable. Consequently, ULD-CT images reconstructed using an IR are suitable and can be tuned further in the future for acceptable use in patients with bone trauma and disorders.